Down-expressed GLT-1 in PSD astrocytes inhibits synaptic formation of NSC-derived neurons in vitro. Issue 1 (2nd January 2019) - Yu, Dafan; Cheng, Zhenxing; Ali, Abdoulaye Idriss; Wang, Jiamin; Le, Kai; Chibaatar, Enkhmurun; Guo, Yijing
ABSTRACT: Little is known about the effect of astroglial GLT-1 of post-stroke depression (PSD) rat model on the function of neural stem cells (NSCs). This study aimed to investigate whether astroglial GLT-1 of PSD rats affect differentiation of NSCs from neonatal rat hippocampus and synaptic formation of NSC-derived neurons. Astrocytes were isolated from the left hippocampus of normal adult SD rats and PSD rats. A lentiviral vector was used to silence the expression of GLT-1 in astrocytes of PSD rats. NSCs were respectively co-cultured with normal (control), PSD, and GLT-1 silenced astrocytes for 7 days. GLT-1, GFAP, MAP2, Synaptophysin (SYN), glutamate (Glu) and glutamine (Gln) were respectively measured by qRT-PCR, western blot, immunofluorescence and efficient mass spectrometry (MS). PSD astrocytes increased the number of NSC-derived astrocytes, but inhibited the expression of GLT-1 of NSC-derived astrocytes and synapses of NSC-derived neurons. On the basis of the low expression of GLT-1 in PSD astrocytes, we further silenced GLT-1 in PSD astrocytes. Interestingly, GLT-1 silenced PSD astrocytes more obviously inhibited synapses of NSC-derived neurons, but increased the number of NSC-derived neurons and reversed the expression of GLT-1 in NSC-derived astrocytes. At the same time, concentration of glutamate in the medium elevated, and glutamine in the medium gradually reduced. In NSC-derived neurons and astrocytes, glutamate metabolism was also affected by changed GLT-1. Down-expressed GLT-1 in PSD astrocytes stimulated NSCs differentiating into astrocytes, but inhibiting the formation of functional synapses by influencing glutamate metabolism in vitro.